In-depth review of five fatigue measures in shift workers. Issue 1 (2nd January 2016) - Sagherian, Knar; Geiger Brown, Jeanne
Abstract : Background: Occupational fatigue is commonly reported in shift-working populations. In the literature, there are several well-known fatigue measures that are regularly used to assess either general or specific aspects of employee fatigue. Purpose : The purpose of this paper was to provide an in-depth review of five fatigue instruments frequently used in occupational science over the past two decades. These instruments are: the Checklist Individual Strength, the Fatigue Assessment Scale, the Need for Recovery, the Occupational Fatigue Exhaustion Recovery, and the Swedish Occupational Fatigue Inventory scales. We describe each instrument in detail, including how it was developed and validated, how it can be obtained, psychometric data, and its use in occupational studies. Conclusion : These instruments provide an understanding of fatigue either as a unidimensional or multidimensional construct. Overall, the five measures are brief (10–20 items), user-friendly, and have minimal respondent and administrative burden. They are reliable and valid based on the psychometric studies in the working population. Each measure has the potential to be utilized as a surveillance tool in monitoring employee fatigue and ensuring workplace safety. Selecting one or combination of these measures depends on the researcher's conceptual and operational definitions of fatigue, and the study objectives.